Team building in the workplace. Creative people in Portugal - Ribeiro, Luisa (2013)
Numerous studies have been done about creative people. Some of these studies point to the importance of cultural differences between countries that might enhance or block creative achievement. The authors study Portuguese people whose work has been recognized as creative in the past 6 years, looking for particularities in their psychological makeup and work style. The current work presents the preliminary results that point to great similarities with the reviewed literature (teamwork, informal relationships, peer feedback, mentors or inspiring figures, action centred, intrinsic motivation, constant dedication, work life balance, match between the challenges and the growing competences, error acceptance, domain knowledge and humility). However the participants also refer that the quality of their work is much more easily recognized abroad.